Pengaruh Stres Kerja Dan Konflik Kerja Terhadap Kinerja Karyawan PT. Sumber Alfaria Trijaya Tbk Cabang Banjarmasin - Hairiyah; Taharuddin; Muhammad Hasanur Arifin (Smart Business Journal (SBJ), 2022)
This study aims to investigate the impact of corporate culture and job satisfaction on employee performance. Because it explores causality between variables, this study employs a quantitative technique. The saturated sample technique was used to choose a sample of 44 employees from PT Arutmin Indonesia Tambang kintap. A questionnaire was used to collect data, then analyzed using multiple regression. The study's findings show that organizational culture has a positive and significant effect on employee performance, with a considerable influence of 0.552 percent, and that work satisfaction has a positive and significant effect on employee performance, with a considerable influence of 0.361%. The findings show that corporate culture and work satisfaction considerably influence employee performance, with a strong effect of 0.738, or 73.8%.